Modified phenol-formaldehyde resins and their application in bitumen-polymeric mixtures - Strap, Galyna; Astakhova, Olena; Lazorko, Olexander; Shyshchak, Oleh; Bratychak, Michael (Publishing House of Lviv Polytechnic National University, 2013)
Phenol-formaldehyde resins (PhFR) with reactive methacrylate fragments or labile peroxy bonds in the side branches used as a polymeric component of bitumen-polymeric mixtures have been investigated. Taking into account that PhFR with peroxy fragments based on epoxy resin does not described in literature, its synthesis procedure has been developed. The kinetic regularities of the reaction between peroxy derivative of epoxy resin (PDER) and phenol group of PhFR were studied taking the reaction of PDER with phenol as an example. The structure of PhFR with peroxy groups (PhFRP) has been confirmed by IR-studies. Bitumenpolymeric mixtures with PhFRP or PhFR with unsaturated fragments (PhFRU) in the amount of 1, 3, 5 or 7 mass parts per 100 g of petroleum bitumen were examined at 443, 463 or 483 K for 0.5, 1.0 or 2.0 h. The composition of bitumn-polymeric mixtures has been determined using the group analysis. Вивчена можливість використання як полімерного компоненту бітум-полімерних сумішей фенол-формальдегідних смол (ФФС), які містять у бічних відгалуженнях реакційноздатні метакрилатні фрагменти або лабільні пероксидні зв’язки. Враховуючи те, щоФФСз пероксидними фрагментами на основі епоксидної смоли в літературі не описана, розроблена методика її синтезу. Кінетичні закономірності реакції між пероксидною похідною епоксидної смоли (ППЕС) і фенольною групою ФФС вивчені на прикладі ППЕС з фенолом. Структура ФФС з пероксидними групами (ФФСП) підтверджена ІЧ- спектроскопічними дослідженнями. Бітум-полімерні суміші, що містили ФФСП або фенол-формальдегідну смолу з ненасиченими фрагментами (ФФСН) в кількості 1, 3, 5 чи 7 мас.част. на 100 г нафтового бітуму вивчені за температур 443, 463 або 483 К впродовж 0,5, 1,0 чи 2,0 год. З використанням структурно-групового методу аналізу встановлено склад бітум-полімерних сумішей.
Модифіковані фенол-формальдегідні смоли та їх застосування у бітум-полімерних сумішах
Keywords: phenol-formaldehyde resin; modification; peroxide; unsaturated bond; kinetics; IR-spectroscopy; bitumen-polymeric mixtures; group analysis; фенол-формальдегідна смола; модифікація; пероксид; ненасичені зв’язки; кінетика; ІЧ-спектроскопія; бітум-полімерні суміші; структурно-груповий аналіз